A brief history of meat in the human diet and current health implications. (October 2018) - Mann, Neil J.
Abstract: Anthropological investigations have confirmed many times over, through multiple fields of research the critical role of consumption of animal source foods (ASF) including meat in the evolution of our species. As early as four million years ago, our early bipedal hominin ancestors were scavenging ASFs as evidenced by cut marks on animal bone remains, stable isotope composition of these hominin remains and numerous other lines of evidence from physiological and paleo-anthropological domains. This ASF intake marked a transition from a largely forest dwelling frugivorous lifestyle to a more open rangeland existence and resulted in numerous adaptations, including a rapidly increasing brain size and altered gut structure. Details of the various fields of anthropological evidence are discussed, followed by a summary of the health implications of meat consumption in the modern world, including issues around saturated fat and omega-3 fatty acid intake and discussion of the critical nutrients ASFs supply, with particular emphasis on brain function.